NanoCarbon 2011 Selected works from the Brazilian Carbon Meeting - Avellaneda, Cšar. (Carbon Nanostructures, 2013)
This book presents highlighted results coming up from NanoCarbon2011, a Brazilian Carbon event. The topics cover the latest advances in Brazilian basic and applied research related to different carbon materials. The chapters address reviews on their fundamental and outstanding properties and describe various classes of new promising high-tech applications for carbon materials.